2021
DOI: 10.1080/20008198.2021.1881728
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidelines for online Narrative Exposure Therapy (e-NET) – a short-term treatment for posttraumatic stress disorder adapted for remote delivery

Abstract: Background: Online therapy has become increasingly desirable and available in recent years, with the current COVID-19 pandemic acting as a catalyst to develop further protocols enabling therapists to conduct online treatment safely and efficaciously. Offering online treatment potentially means that treatments are available to clients who would otherwise have no access, closing the gap in the provision of mental health services worldwide. Objective: This paper focuses on practical guidelines using online Narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Furthermore, few adaptations were reported as a function of clients’ age or disorder, although some authors ( Smith et al, 2020 ; Van Daele et al, 2020 ) emphasise that teleconsultation be adapted to the population, its context, and the conditions they are facing. Other authors and clinicians provide recommendations on how to adapt therapeutic interventions to the teleconsultation setting for groups ( Banbury et al, 2018 ), children ( American Academy of Children and Adolescent Psychiatry, 2021 ; American Psychiatric Association, 2020 ; Becqueriaux, 2020 ; Landrum, 2020 ), as well as for people suffering from eating disorders ( Waller et al, 2020 ) and post-traumatic stress ( Kaltenbach et al, 2021 ; Moring et al, 2020 ). Nevertheless, such works are still in their infancy and more empirical evidence is needed to optimise the provision of teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few adaptations were reported as a function of clients’ age or disorder, although some authors ( Smith et al, 2020 ; Van Daele et al, 2020 ) emphasise that teleconsultation be adapted to the population, its context, and the conditions they are facing. Other authors and clinicians provide recommendations on how to adapt therapeutic interventions to the teleconsultation setting for groups ( Banbury et al, 2018 ), children ( American Academy of Children and Adolescent Psychiatry, 2021 ; American Psychiatric Association, 2020 ; Becqueriaux, 2020 ; Landrum, 2020 ), as well as for people suffering from eating disorders ( Waller et al, 2020 ) and post-traumatic stress ( Kaltenbach et al, 2021 ; Moring et al, 2020 ). Nevertheless, such works are still in their infancy and more empirical evidence is needed to optimise the provision of teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…NET is a well-established exposure-based intervention for PTSD (Schauer, Neuner, & Elbert, 2011 ). eNET is adapted for the use in a video call setting (Kaltenbach et al, 2021 ; Robjant, Meyer, Kaiser, Kaltenbach, & Schauer, 2020 ). Adaptations are mainly made in order to provide comparable content via video calls (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that paraprofessionals can be effectively trained to administer NET (Jacob, Neuner, Maedl, Schaal, & Elbert, 2014 ; Köbach, Schaal, Hecker, & Elbert, 2017 ; Neuner et al, 2008 ). Most recently, recommendations have been published how to use NET via video calls (eNET; Kaltenbach et al, 2021 ). However, studies showing the efficacy of eNET still need to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…For these case studies, clients had an average of 12 sessions. The protocol for treatment was developed with consideration for guidelines in conducting NET via telehealth (Kaltenbach et al, 2021).…”
Section: Net Intake and Therapy Protocolmentioning
confidence: 99%